If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2ln(5x + 1) = 14 Reorder the terms: 2ln(1 + 5x) = 14 (1 * 2ln + 5x * 2ln) = 14 (2ln + 10lnx) = 14 Solving 2ln + 10lnx = 14 Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Reorder the terms: -14 + 2ln + 10lnx = 14 + -14 Combine like terms: 14 + -14 = 0 -14 + 2ln + 10lnx = 0 Factor out the Greatest Common Factor (GCF), '2'. 2(-7 + ln + 5lnx) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(-7 + ln + 5lnx)' equal to zero and attempt to solve: Simplifying -7 + ln + 5lnx = 0 Solving -7 + ln + 5lnx = 0 Move all terms containing l to the left, all other terms to the right. Add '7' to each side of the equation. -7 + ln + 7 + 5lnx = 0 + 7 Reorder the terms: -7 + 7 + ln + 5lnx = 0 + 7 Combine like terms: -7 + 7 = 0 0 + ln + 5lnx = 0 + 7 ln + 5lnx = 0 + 7 Combine like terms: 0 + 7 = 7 ln + 5lnx = 7 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 12a-11=15a-10 | | 10z+4=1 | | 3(x+4)-12x=48 | | lnx=70.0173683 | | 2q+5y+4z=0 | | 8h-24=36 | | 12x-11=15x-10 | | 12=(n-1)(n-2)(n-3)(n-4)(n-5)-3n^2 | | -36=y-5y-21 | | 12=(n-1)(n-2)(n-3)(n-4)-(2n^3) | | 12=n^4-12n^3+35n^2-50n+24 | | 8+4x=7x | | -11-5X=-111 | | (y+3)2=25 | | 8x=20x^2 | | 18x-5y=90 | | -6+w+w=9+w | | 2y-y-9y= | | y=1E+06x+2E+06 | | 3x+2x+x-3=27 | | 3+8y=3(2x)-1 | | 12-2y=8(y+4) | | 12-2y=8(x+4) | | X(X-8)=1280 | | 5x+16=3x+42 | | 5(2x-7)=3x | | 8e-8=64 | | x+3+2x=63 | | 7(a+4)=77 | | 2x+3=8x-39 | | -13x+8=-96 | | 2b+7a+4=(b+a)(b-a) |